2018
DOI: 10.1097/sga.0000000000000345
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Transition in Pediatrics and Young Adults With Inflammatory Bowel Disease

Abstract: The incidence of inflammatory bowel disease has steadily increased in children within the last decade. As young adults transition into the adult healthcare system, lack of support can lead to disease exacerbations and disease-related complications. The purpose of this scoping review was to examine the current healthcare transition literature in pediatrics and young adults with inflammatory bowel disease, with a particular focus on assessment or screening tools to evaluate healthcare transition readiness. Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…Thirdly, the transition process to the management in adulthood of people with IBD might focus on the promotion of the patient's self-management and engagement, implementing the appropriate usage of monitoring tools [ 96 , 97 ]. Due to the continued evolution of the needs, it could be important to build also a transitional IBD-Clinic managed by the collaboration between adult and pediatric professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the transition process to the management in adulthood of people with IBD might focus on the promotion of the patient's self-management and engagement, implementing the appropriate usage of monitoring tools [ 96 , 97 ]. Due to the continued evolution of the needs, it could be important to build also a transitional IBD-Clinic managed by the collaboration between adult and pediatric professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results demonstrated that children's disease knowledge was negatively associated with parent's physical functioning. It was established that parents were too careful when shifting responsibility for disease‐management to children (Rohatinsky et al., 2018). Although children may have disease knowledge, parents were still committed to caring for their children, which may increase parents' stress levels and elicit less confident parenting.…”
Section: Discussionmentioning
confidence: 99%
“…Children's QoL is regarded as a multidimensional construct, including physical, emotional, social and school functioning (Wu et al., 2013). A scoping review and intervention research suggested that QoL should be considered as a critical outcome indicator to reflect the adaptation in the process of transition readiness (Rohatinsky et al., 2018; Skov et al., 2018). Prior observational research have shown that practical transition readiness was a vital predictor that could improve children's QoL by providing knowledge and improving the self‐management of diseases for children (Ma et al., 2018; Sheng et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, the transition process to the management in adulthood of IBDs might focus on the promotion of the patient's self-management and engagement, implementing the appropriate usage of monitoring tools (89,90). Due to the continue evolution of the needs, it could be important to build also a transitional IBD-Clinic managed by the collaboration between adult and pediatric professionals.…”
Section: Discussionmentioning
confidence: 99%